Sodium Acetate and Vacuum Packaging to Improve Shelf Life of Refrigerated Lethrinus lentjan Fillets - R., Shalini; G., Indra Jasmine; S.A., Shanmugam; K., Ramkumar (Fishery Technology, 2025)
The shelf life of vncuum packed fresh Lethrinus lentjan fillets, untreated or treated with various levels of sodium acetate, was evaluated. The quality was assessed periodically by selected biochemical, microbiological and sensory characteristics. The shelf life of product packed without vacuum and untreated vacuum-packed fillets was around 7-8 days whereas sodium acetate treated fillets had shelf life of 2-3 weeks. Reduced rate of bacterial growth, decreased rate of production of TMA-N and TVB-N and delayed development of off odours were observed in sodium acetate treated, vacuum packed fillets.